Blockchain in Higher Education: A Systematic Review of Integration Frameworks and Adoption Challenges - Abdul Samee; Endah Sudarmilah; Yusuf Sulistyo Nugroho (Universitas PGRI Kanjuruhan Malang, 2026)
Blockchain has emerged as a promising infrastructure to address persistent inefficiencies in higher education systems, particularly within Learning Management Systems (LMS) and administrative processes, due to its potential to improve transparency, security, and operational efficiency. This review conducts a Systematic Literature Review (SLR), following PRISMA 2020 guidelines, to evaluate blockchain integration approaches in academic contexts. Unlike previous reviews, this review specifically synthesizes literature published between 2020 and 2025, providing a timely and focused analysis of recent advancements. A total of 41 peer-reviewed articles were selected and directly cited in this review. The analysis investigates implementation frameworks, practical use cases, and the technological, organizational, and regulatory factors influencing adoption. Key findings reveal that blockchain facilitates secure credentialing, decentralized identity verification, learner autonomy, and institutional transparency. However, significant barriers such as scalability limitations, legal uncertainty, and interoperability challenges continue to hinder widespread deployment. This review provides a comprehensive synthesis of current practices and offers actionable, research-informed recommendations for policymakers, technology developers, and higher education institutions aiming to implement blockchain-driven solutions.